(untitled) (Dhaka University Journal of Science, 2016)
This paper concerns the unsteady mixed convection laminar boundary layer flow past a vertical wedge in the presence of thermal radiation. The governing equations have been solved by the straightforward finite difference method for the entire frequency range. We observe that the Richardsons number, Ri, strongly affects the skin friction, heat transfer and mass transfer. The effect of the Schmidt number, Sc, on the mass transfer is significant, whereas the skin friction and the heat transfer are almost unaffected by it. Also the heat transfer is considerably dependent on the conduction-radiation parameter, Rd, but the influence of this parameter on the skin friction and the mass transfer is rather weak. Dhaka Univ. J. Sci. 64(1): 59-64, 2016 (January)